Consumer and Food Protection: Study on Supervision of Food in Circulation by LOKA POM Surakarta - Wafi Imtinan Raihan Nita; Kelik Wardiono (Universitas Muhammadiyah Surakarta, 2023)
Consumers in meeting their needs are very dependent on business actors. There is a need for legal protection which is an effort to fulfill rights by providing compensation, testimonials, medical services and legal assistance. The research method uses a non‐doctrinal approach, which is normative, looking for the right answer by showing the truth sought or through social facts that interpret the law as it is interpreted and are part of the context of reality that exists in society. Primary and secondary data are the results of surveillance of circulating food at LOKA POM Surakarta and literature studies. The data that has been collected will then be analyzed qualitatively using deductive logic. BPPOM Supervision of Food Circulation in Surakarta based on the way of supervision is divided into 2, namely: (a) Pre‐Market, where supervision is still within the scope of its production; (b) Post Market, where supervision has been circulating in the field. Supervision of Food Product Quality and Safety, as well as Food Packaging at the POM Workshop in Surakarta City consists of several activities, including: (1) Product Sampling and Testing Activities; (2) Activities of Inspecting Food Production Facilities; (3) Food Distribution Facility Supervision Activities and based on activities carried out by LOKA POM Surakarta are appropriate and provide legal protection for consumers.